2008
DOI: 10.1161/circulationaha.107.715649
|View full text |Cite|
|
Sign up to set email alerts
|

C1-Esterase Inhibitor Protects Against Neointima Formation After Arterial Injury in Atherosclerosis-Prone Mice

Abstract: Background-Although activation of the complement system has been implicated in the progression of human atherosclerosis, its function during arterial remodeling after injury has not been investigated. Here, we examined the contribution of the complement cascade to neointima formation in apolipoprotein E-deficient mice using a C1-esterase inhibitor (C1-inhibitor). Methods and Results-Apolipoprotein E-deficient mice fed an atherogenic diet were subjected to wire-induced endothelial denudation of the carotid arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 53 publications
0
44
0
2
Order By: Relevance
“…19 First reports suggest similar effects of locally produced complement components over the course of not only ischemia/reperfusion injury but also during development of atherosclerosis and neointima formation after arterial injury. 17,18,20,21 The ostensible contradiction that remains regarding either a proatherogenic or antiatherogenic effect of MBL in atherosclerosis led us to investigate basic MBL characteristics over the course of atherogenesis in atherosclerosis-prone mice and human atherosclerotic lesions. Our data demonstrate the presence and distribution of MBL in experimental and human atherosclerotic lesions and provide compelling evidence for a controlling role of local myeloid-derived MBL expression in atherosclerosis development.…”
Section: Clinical Perspective P 2195mentioning
confidence: 99%
“…19 First reports suggest similar effects of locally produced complement components over the course of not only ischemia/reperfusion injury but also during development of atherosclerosis and neointima formation after arterial injury. 17,18,20,21 The ostensible contradiction that remains regarding either a proatherogenic or antiatherogenic effect of MBL in atherosclerosis led us to investigate basic MBL characteristics over the course of atherogenesis in atherosclerosis-prone mice and human atherosclerotic lesions. Our data demonstrate the presence and distribution of MBL in experimental and human atherosclerotic lesions and provide compelling evidence for a controlling role of local myeloid-derived MBL expression in atherosclerosis development.…”
Section: Clinical Perspective P 2195mentioning
confidence: 99%
“…Further studies will also be needed to delineate the effects of agents found to be protective in other arterial disease models, such as C1 esterase inhibitor. 62 Expression of complement proteins and complement regulators has been well documented in human atherosclerosis, underscoring the importance of understanding the details of complement biology in the arterial wall via analysis of mouse models. 63 DAF is not expressed on normal VSMC but can be identified on VSMC as well as macrophages in advanced plaques, and is functionally competent as a complement regulator ex vivo.…”
Section: 53mentioning
confidence: 99%
“…In vessels, the complement system may be activated by antigenantibody immune complexes, CRP, modified lipoproteins, apoptotic cells, and cholesterol crystals. Because C3 is the central component in complement activation, inhibition of C3 activation leads to the blockade of biologically active end products, including C5b-9, C5a, and C3a, 13,14 as well as the retardation of atherosclerosis. 15 It has been widely appreciated that CRP is more than a biomarker of inflammation.…”
Section: Discussionmentioning
confidence: 99%